2004
DOI: 10.1164/rccm.200407-885oc
|View full text |Cite
|
Sign up to set email alerts
|

Moxifloxacin-containing Regimens of Reduced Duration Produce a Stable Cure in Murine Tuberculosis

Abstract: In a recent experimental study using the mouse model of tuberculosis, treatment with a combination of rifampin, moxifloxacin, and pyrazinamide was able to shorten the time to negative lung cultures by up to 2 months compared with the standard regimen of rifampin, isoniazid, and pyrazinamide. To confirm that this substitution of moxifloxacin for isoniazid permits a shorter duration of treatment, a second study was performed in which mice were assessed for relapse after treatment with combination therapy for 3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
173
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 211 publications
(182 citation statements)
references
References 14 publications
9
173
0
Order By: Relevance
“…Drugs were obtained and stock solutions were prepared as previously described (16). RPT tablets, donated by Sanofi-Aventis (Kansas City, MO), were ground into a powder and suspended in water before gavage.…”
Section: Antimicrobialsmentioning
confidence: 99%
See 3 more Smart Citations
“…Drugs were obtained and stock solutions were prepared as previously described (16). RPT tablets, donated by Sanofi-Aventis (Kansas City, MO), were ground into a powder and suspended in water before gavage.…”
Section: Antimicrobialsmentioning
confidence: 99%
“…Six-week-old female BALB/c mice were purchased from Charles River (Wilmington, MA) and infected as previously described (16). Mice were infected in four consecutive runs.…”
Section: Aerosol Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, due to lower cost, OFX is still being used for the treatment of MDR-TB patients in developing countries. Early studies carried out in murine models of TB suggested that replacement of EMB or INH with MFX in first-line treatment for TB has the potential to improve outcome and to shorten therapy to four months from the current standard of six months [40,41]. The maximum treatment benefit was noted when MFX was used in place of INH in the murine model of TB [40].…”
Section: Fluoroquinolones As Anti-tb Drugsmentioning
confidence: 99%